2013
DOI: 10.1021/ar400130a
|View full text |Cite
|
Sign up to set email alerts
|

Using Functional Nano- and Microparticles for the Preparation of Metal–Organic Framework Composites with Novel Properties

Abstract: A critical materials challenge over the next quarter century is the sustainable use and management of the world's natural resources, particularly the scarcest of them. Chemistry's ability to get more from less is epitomized by porous coordination polymers, also known as metal-organic frameworks (MOFs), which use a minimum amount of material to build maximum surface areas with fine control over pore size. Their large specific surface area and tunable porosity make MOFs useful for applications including small-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
166
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(169 citation statements)
references
References 58 publications
1
166
0
Order By: Relevance
“…32,33 These approaches involve the addition of preformed functional species into the MOF precursor solution and the subsequent in situ formation of MOF crystals with embedded functional particles. Furthermore, it has been demonstrated that the heterospecies can improve the kinetics of MOF formation, [34][35][36] as nano-and micro-particles can act as crystallization facilitators promoting faster MOF growth. On the other hand, functional nanoparticles tend to aggregate under the acidic environment created by the dissociation of ligands during this solution process.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 These approaches involve the addition of preformed functional species into the MOF precursor solution and the subsequent in situ formation of MOF crystals with embedded functional particles. Furthermore, it has been demonstrated that the heterospecies can improve the kinetics of MOF formation, [34][35][36] as nano-and micro-particles can act as crystallization facilitators promoting faster MOF growth. On the other hand, functional nanoparticles tend to aggregate under the acidic environment created by the dissociation of ligands during this solution process.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the encapsulation process is widely used to incorporate heteroparticles with new functions into MOFs because the former two methods are limited to covalent bonding and coordination chemistry. Solution impregnation, gas-phase infiltration and solid grinding have been applied to introduce precursors into the preformed MOF host, which is then converted to the corresponding functional components encapsulated in the MOFs 32,33 . However, in this two-step approach, nonselective deposition at the outer surface of the MOF host is unavoidable, and particle size and morphology are limited by the cavities of the MOF host.…”
mentioning
confidence: 99%
“…Recently, another more attractive one-pot approach has been developed that involves the addition of preformed functional particles into the MOF precursor solution and the in situ formation of MOF-encapsulated functional particles during MOF growth 33 . However, nanoparticles (NPs) tend to dissolve or agglomerate under the acidic environment created by the dissociation of ligands during this solution process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the most widely used approach for the property regulation of coordination polymers is structure design via manipulation of the atomic/molecular packing by intermolecular interactions [13][14][15]. Besides the great success achieved on the molecular/atomic scale, the structure design on a mesoscale (10~1000 nm) has recently been recognized as a promising choice [16][17][18][19]. By downsizing of a bulk crystal, the volume ratio of the surface units to the bulk units can be increased significantly, leading to a coupling effect from the bulk structure and the surface units [17,20,21].…”
Section: Introductionmentioning
confidence: 99%